Myth in 300 Strokes Mit v 300 taktih - Pobežin, Gregor; Grdina, Igor (Studia mythologica Slavica, 2019)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">This paper aims to explore the phenomenon of the opera minute which emerged from the avant-garde experimentalism after WWI; its beginner and one of the foremost masters, the French composer Darius Milhaud put three short, eight-minute operas on stage in 1927. Others soon followed, among them the Slovenian composer Slavko Osterc who composed the opera-minute “Medea” in 1932. This paper is the first to transcribe in length the manuscript of Osterc’s “Medea”, comparing it to Euripides’ original. Furthermore, the article aims to establish the fine similarities and distinctions between the approach regular opera took towards myth and that of the avant-garde opera-minute.